STRATEGI KOMUNIKASI KANTOR CAMAT SIMPANG EMPAT DALAM MENSOSIALISASIKAN PROGRAM E-LAPOR! KEPADA MASYARAKAT DI KECAMATAN SIMPANG - Emmelia A. Ginting; Sri Menda Krina Br Ginting (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
This study aims at determining the communication strategies used by the Simpang Empat District Office in socializing the E-LAPOR! to the community in the district. The research subjects are apparatus of Simpang Empat sub-district, people who had received and had not received socialization. The object of research is the Communication Strategy in terms of Planning, Implementation and Evaluation and Communication Strategy Techniques which consist of Redundancy (Repetition), Informative, Persuasive, and Educative.Data collection techniques through research in the field using observation and in-depth interviews with research informants and using literature or documents that support the research. Data processing is done by applying a qualitative descriptive approach.The results of the descriptive analysis showed that the socialization efforts carried out by the Simpang Empat Tanah Karo sub-district have not been optimal, especially in the field of redundancy (repetition) techniques, namely repeating messages to the public, where there were still residents who have received socialization but often forgetton how to use the application. It was also seen that the Persuasive Technique has not been fully successful in influencing the community so that the benefits of this program have not been able to bind a large number of audiences/communities. Likewise with Informative and Educational Techniques which were still not implemented so that the public were not familiar and active by sending SMS to this application. In addition, the biggest obstacle to socialization efforts is hampered by the emergence of the Covid-19 Pandemic, so that efforts to disseminate two-way communication were temporarily halted following the Health Protocol Directive set by the Central Government. SimpangEmpat District should continued to launch its Communication Strategy by using various media such as banners, billboards, and banners which were still trying to introduced this program to stay closer to the community and can also use the Village Apparatus as an extension of the Sub-district's arm in introducing the E-LAPOR application ! to the Village community in Simpang Empat Tanah Karo District.